2020
DOI: 10.1001/jamadermatol.2020.0112
|View full text |Cite
|
Sign up to set email alerts
|

Residency Education on Sexual and Gender Minority Health

Abstract: Dermatologists play a significant and multifaceted role in caring for sexual and gender minority (SGM) patients, an expansive population that includes individuals who identify as lesbian, gay, bisexual, asexual, queer, transgender, and gender nonconforming and those with differences in sex development. Multiple social determinants, including stigma and discrimination in health care and a lack of knowledgeable clinicians, have created health inequities for SGM individuals, leading the National Institutes of Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…19 Dermatology residency programs should work to close gaps in SGM education in their curriculum and provide trainees with best practices for caring for SGM patients with CISDs (eg, the use of patient-preferred language, offering treatment options for CISDs that are consistent with the gender-affirming goals of SGM patients who may be transitioning). [20][21][22] Our finding that non-Hispanic White SGM women with CISDs, but not non-Hispanic Black or Hispanic/Latino non-SGM women, were significantly more likely than non-Hispanic White non-SGM women to report not always being treated with respect by health care practitioners could reflect how SGM status is not outwardly apparent to practitioners like race and ethnicity may be; this finding underscores the need for the routine collection and reassessment of sexual orientation, gender identity, and pronoun information in addition to racial and ethnic identity data. 23 By universally collecting this demographic information from all patients and taking the time to better understand the unique background, values, and goals of each of their patients, dermatologists can be better prepared to provide culturally responsive care to SGM patients with CISDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Dermatology residency programs should work to close gaps in SGM education in their curriculum and provide trainees with best practices for caring for SGM patients with CISDs (eg, the use of patient-preferred language, offering treatment options for CISDs that are consistent with the gender-affirming goals of SGM patients who may be transitioning). [20][21][22] Our finding that non-Hispanic White SGM women with CISDs, but not non-Hispanic Black or Hispanic/Latino non-SGM women, were significantly more likely than non-Hispanic White non-SGM women to report not always being treated with respect by health care practitioners could reflect how SGM status is not outwardly apparent to practitioners like race and ethnicity may be; this finding underscores the need for the routine collection and reassessment of sexual orientation, gender identity, and pronoun information in addition to racial and ethnic identity data. 23 By universally collecting this demographic information from all patients and taking the time to better understand the unique background, values, and goals of each of their patients, dermatologists can be better prepared to provide culturally responsive care to SGM patients with CISDs.…”
Section: Discussionmentioning
confidence: 99%
“…A 2020 survey of US dermatology residency programs showed that 46% of programs have 0 hours of SGM education in their curriculum . Dermatology residency programs should work to close gaps in SGM education in their curriculum and provide trainees with best practices for caring for SGM patients with CISDs (eg, the use of patient-preferred language, offering treatment options for CISDs that are consistent with the gender-affirming goals of SGM patients who may be transitioning) …”
Section: Discussionmentioning
confidence: 99%
“…Dermatologists play a pivotal role addressing these needs and providing services for gender-affirming care (GAC), such as laser hair removal, management of androgenetic alopecia, injectable neurotoxins, or soft tissue augmentation. To ensure culturally competent care, dermatology residency programs should provide/promote didactic and experiential training tailored to the health needs of TGD patients [ 2 ]. Additionally, prospective residents may benefit from being able to ascertain whether certain programs are involved in GAC, including education and research.…”
Section: Introductionmentioning
confidence: 99%